Influencer marketing and e-wom: the combination of digital powers that drive cosmetic product purchase decisions - Andi, Andi; Sutejo, Bambang; Rizki, Mela Novita; Aldo, Muhammad (Jurnal Mantik, 2025)
The purpose of this study was to analyze the extent to which influencer marketing and electronic word of mouth (E-WOM) simultaneously influence consumer purchasing decisions. This research employed a quantitative approach with a survey method. Data were collected through questionnaires distributed to 100 respondents who had purchased or used cosmetic products after being exposed to influencer marketing and E-WOM, selected using purposive sampling. Data analysis was conducted using multiple linear regression to determine the influence of the independent variables (influencer marketing and E-WOM) on the dependent variable (purchase decision). The findings reveal that influencer marketing and E-WOM significantly affect consumer purchasing decisions, with a combined contribution of 56.9%. This result highlights the novelty of integrating both digital strategies as complementary drivers of consumer behavior in the cosmetic industry, particularly in an era where peer-to-peer communication and digital endorsements increasingly shape purchase intentions. From an academic perspective, this study enriches the literature on digital marketing by demonstrating how the synergy between influencer credibility and electronic word-of-mouth creates a stronger explanatory framework for understanding purchasing decisions. Practically, the findings imply that cosmetic brands should not only optimize influencer collaborations but also design strategies that stimulate authentic consumer engagement to enhance E-WOM, thereby achieving a sustainable competitive advantage in digital marketplaces.